2015
DOI: 10.1016/j.ssresearch.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence, substance use, and neighborhood context

Abstract: Adolescent exposure to violence and substance use are both public health problems, but how neighborhood context contributes to these outcomes is unclear. This study uses prospective data from 1,416 adolescents to examine the direct and interacting influences of victimization and neighborhood factors on adolescent substance use. Based on hierarchical Bernoulli regression models that controlled for prior substance use and multiple individual-level factors, exposure to violence significantly increased the likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 90 publications
(148 reference statements)
3
28
0
4
Order By: Relevance
“…On the other hand, other studies indicate that earlier substance use is indeed associated with later violence (Wanner et al, 2009; Wei, Loeber, & White, 2004; White & Hansell, 1998), but that earlier violence is not related to later substance use. Several studies report support for the counter direction: Violence involvement predicts later substance use (Fagan, Wright, & Pinchevsky, 2015; Wright, Fagan, & Pinchevsky, 2013). Furthermore, two studies using longitudinal data found that effects of violence on substance use are influential in the short term (i.e., within the same period), but not in the long term (i.e., 5 years later; Miller, Fagan, & Wright, 2014; Thompson, Sims, Kingree, & Windle, 2008).…”
Section: Longitudinal Associationsmentioning
confidence: 99%
“…On the other hand, other studies indicate that earlier substance use is indeed associated with later violence (Wanner et al, 2009; Wei, Loeber, & White, 2004; White & Hansell, 1998), but that earlier violence is not related to later substance use. Several studies report support for the counter direction: Violence involvement predicts later substance use (Fagan, Wright, & Pinchevsky, 2015; Wright, Fagan, & Pinchevsky, 2013). Furthermore, two studies using longitudinal data found that effects of violence on substance use are influential in the short term (i.e., within the same period), but not in the long term (i.e., 5 years later; Miller, Fagan, & Wright, 2014; Thompson, Sims, Kingree, & Windle, 2008).…”
Section: Longitudinal Associationsmentioning
confidence: 99%
“…This method has already been used in other fields but, to the authors' knowledge, has so far not been applied to mass valuation. Hierarchical linear models have been successfully used since the 80s in the fields of education (Aitkin et al 1981;Raudenbush and Bryck 1986;Singh 2014), public policy (Duncan et al 1993;Tso and Guan 2014), criminology (Gelman 2007;Fagan et al 2015), and politics (Wang et al 2015). This method overcomes some limitations of the traditional regression models, which are based on the hypothesis that the individuals in the sample are independent, however this assumption is not always correct.…”
Section: Introductionmentioning
confidence: 99%
“…This methodology has already been used in other fields like education (Singh, 2014), public policy (Tso & Guan, 2014), politics (Wang, Rothschild, Goel & Gelman, 2014) or criminology (Fagan, Wright & Pinchevsky, 2015).…”
Section: Proposed Methodology: the Hierarchical Linear Modelmentioning
confidence: 99%